Sleep Hygiene Counseling During the Covid-19 Pandemic To The Community In the Marga Tabanan village - Rahyanti, Ni Made Sri; Sriasih, Ni Kadek (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institute Teknologi dan Kesehatan (ITEKES) Bali, 2021)
WHO has declared Covid-19 to be a global pandemic that has occurred in many countries around the world. Clean and healthy living behavior is the key to preventing the transmission of Covid-19. PHBS consists of hand washing, consumption of healthy food, exercise and adequate rest. Adequate rest can be obtained through healthy sleep (Sleep Hygiene). Healthy sleep education is also one of the interventions in fatigue management that is useful for improving the ability to move. Based on the above, the authors are interested in doing community service in the form of healthy sleep counseling or Sleep Hygiene. The purpose of this counseling is to increase public knowledge about healthy sleep. Counseling was given to 35 people in the community. Based on the results of data analysis, it was found that there was an increase in public knowledge about healthy sleep from before and after being given counseling. The median knowledge of the community before counseling was 16.00 with a minimum value of 5 and a maximum of 15. The median knowledge after counseling was 19 with a minimum value of 16 and a maximum of 20. Based on this, promotive and preventive efforts to reduce fatigue and improve functional status must continue to be carried out so that endurance the body of the community is maintained and protected from the disease covid-19.